Quantum marketing mastering the new marketing mindset for tomorrow's consumers - Rajamannar, Raja (HarperCollins Leadership, an imprint of HarperCollins, 2021)
"As technology has continually evolved in the last several decades, marketing has had to change with it, evolving through four significant stages that build on the strategies and tools of the previous era. What happens next in the fifth stage, or Fifth Paradigm, will not be an evolution, but a revolution. Almost everything about how marketing is done today, including the very notion of a brand itself, will require a complete re-imagination. As Chief Marketing Officer of Mastercard--one of the world's most recognizable and decorated brands--Raja Rajamannar shares the forward-thinking ways all businesses must rethink their entire marketing landscape to remain relevant and be successful." -- Amazon.com.